Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
x = 3
y = 2
Step-by-step explanation:
Equations
7x - 7y = 7
-4x - 7y = - 26 Multiply both sides of the equation by - 1
-1(-4x - 7y = - 26)
4x + 7y = 26
Solution
Add the two equations together
7x - 7y = 7
4x + 7y = 26
11x = 33 Divide by 11
11x/11 = 33/11
x = 3
4x + 7y= 26 Use this equation to solve for y. Use x = 3
4*3 + 7y = 26 Combine the left
12 + 7y = 26 Subtract 12 from both sides
12 - 12 + 7y = 26 - 12 Combine
7y = 14 Divide by 7
7y/7 = 14/7
y = 2
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.